Forensic reporting of a case of sexual abuse broadcast on periscope - Nasiroglu S; Cimen D (Neuropsychiatric Disease and Treatment, 2016)
Serhat Nasıroğlu,1 İrem Damla Çimen2 1Department of Child and Adolescent Psychiatry, Sakarya University Faculty of Medicine, 2Department of Child and Adolescent Psychiatry, Sakarya University Research and Training Hospital, Sakarya, Turkey Abstract: Children who are investigated or prosecuted for an action that is considered a crime by the law, or children who were placed in security facilities due to his/her actions are defined as “children forced into crime”. The period between ages 12–18 years is adolescence, during which crime rates are relatively high. The incidence of sexual behavior of adolescents on social media, which may be considered a crime, has increased in recent years due to technological improvements and increase in the use of social media. Also, the crime rates involving adolescents have increased due to environmental influences, familial factors, and mental disorders. Mental disorders such as conduct disorder, attention deficit hyperactivity disorder, and mood disorders have been found to be associated with sexual abuse in young persons in previous literature. In this study, we present the case of a boy who sexually abused his younger brother at the age of 14 years 2 months and broadcast this abuse on “Periscope”. In this case study, we aimed to discuss the relationships between sexual abuse, social media, and psychiatric disorders. Keywords: social media, child, sexual abuse